SELLING OR SAVING: SUSTAINABLE TOURISM IN WORLD HERITAGE SITES - Wang, Bolin (2007)
The proposed paper will present an exploratory study of World Heritage Sites (WHS) for tourism use. The concept of world heritage was born of the 1972 World Heritage convention. The inscribed sites list is growing rapidly every year, and most World Heritage sites become well-known tourist destinations. This has led to an interest to understand the contemporary use of such sites for tourism purposes, and to examine to what extent they are sustainable in the long term